2014
DOI: 10.1108/imds-11-2013-0482
|View full text |Cite
|
Sign up to set email alerts
|

Green innovation in the automobile industry

Abstract: 2012),"Origins of green innovations: the differences between proactive and reactive green innovations", Management Decision, Vol. 50 Iss 3 pp. 368-398 http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 63 publications
(152 reference statements)
6
57
0
4
Order By: Relevance
“…Findings of this paper found that environmental culture, environmental leadership, environmental capability, the environmentalism of investors and clients and environmental regulations can generate green innovation. Table A4 (see Appendix A) [191][192][193][194][195][196][197][198] presented the results of seven published papers regarding green and ecological innovation based on the author(s) names, year of publication scope and sample of study, area of study, number of sample, respondents, related theory, variables, study purpose, gap and research problem and results and outcome.…”
Section: Breakdown Of Articles Based On Green and Ecological Innovationmentioning
confidence: 99%
“…Findings of this paper found that environmental culture, environmental leadership, environmental capability, the environmentalism of investors and clients and environmental regulations can generate green innovation. Table A4 (see Appendix A) [191][192][193][194][195][196][197][198] presented the results of seven published papers regarding green and ecological innovation based on the author(s) names, year of publication scope and sample of study, area of study, number of sample, respondents, related theory, variables, study purpose, gap and research problem and results and outcome.…”
Section: Breakdown Of Articles Based On Green and Ecological Innovationmentioning
confidence: 99%
“…While Lin et al (2014) describe environmental process innovation as modifications in manufacturing processes and systems with the aim of producing environmentally friendly products capable of meeting eco-targets, such as energy savings, pollution prevention, and waste recycling [15].…”
Section: A Environmental Technological Innovation (Et-innovation)mentioning
confidence: 99%
“…In general, customers do not have natural desire or need for unsustainable product [20], [21]. Therefore, firms need to pay high attention to fulfill customer satisfaction towards their eco-product and gain advantage in the market [15] [16]. Being competitive in the marketplace will open doors for new business opportunity for firms that implement ecoinnovation strategy [22].…”
Section: A Environmental Technological Innovation (Et-innovation)mentioning
confidence: 99%
See 2 more Smart Citations